Transitions in ceramics, a critical account and suggested approach: case-study through comparison of the EBA–MBA and MBA–LBA horizons at Qatna. (April 2014) - Iamoni, Marco
Abstract : In recent years, the concept of transition in Near Eastern archaeology has received considerable attention, in particular in the realm of pottery studies. Despite this renewed interest, little attention has been given to the definition of transition as applied to ceramics in past and current investigations. The aim of this paper is to examine past usage of the idea of transition, to explore its current value in archaeology, and then consider the consequences of this for the interpretation of the archaeological record. In this study old data are combined and compared with new data from excavations at Qatna. This is proposed as a case study for a redefinition of transition in pottery sequences and as a starting point for a re-evaluation of the phenomenon at a more general level.